Urgent desensitization in patients bridged to heart transplantation under extracorporeal membrane oxygenation support: A preliminary experience. Issue 1 (23rd November 2020) - Guihaire, Julien; D'Avino, Serena; Stephan, Francois; Kloeckner, Martin; To, Ngoc Tram; Potier, Agathe; Gaillard, Maïra; Ramadan, Ramzi; Taupin, Jean‐Luc; Le Pavec, Jerome; Deleuze, Philippe
Abstract: Antihuman leukocyte antigen (HLA) antibodies restrict the access to cardiac allografts. Desensitization therapy is a major challenge in patients with cardiogenic shock waiting for urgent heart transplantation (HT). We retrospectively reviewed six patients (mean age of 37.5 years [16–70]) who underwent plasmapheresis (PP) under extracorporeal membrane oxygenation (ECMO) before transplant between January 2017 and September 2018. The average duration of follow‐up was 25 months [20–32]. Mean fluorescence intensity (MFI) of HLA‐specific antibodies was reported as follows: score 4 for MFI < 1000, score 6 for 1000 < MFI < 3000 and score 8 for MFI > 3000. The mean duration of ECMO support was 29 days [1–74] and 6.8 [1–29] PP sessions were performed per patient before transplant. The mean number of HLA‐specific antibodies before HT was 9.6 for score 6 [4–13] and 5.8 for score 8 [1–12]. Four patients had major complications after transplantation (2 hemorrhagic shocks, 5 infectious events). Mean MFI reduction rate was 94% [79–100] for Class I and 44.2% for Class II [0–83]. Hospital survival was 100%, and early antibody‐mediated rejection was diagnosed in one patient at 7 days after HT. Plasmapheresis under ECMO support was associated with favorable early outcomes in highly sensitized candidates for urgent heart transplantation.